Разработка безотходной технологии получения N-метилморфолин-N-оксида (моногидрат) - А. Г. Асратян; Г. А. Багдасарян; А. Дж. Маркосян; С. С. Айоцян; О. С. Аттарян (ՀՀ ԳԱԱ հրատ.)
В предлагаемой работе нами рассмотрен синтез моногидрата N-метилморфолин-N-оксидa (NММО) и предложена технология его синтеза. Предлагаемая технологическая схема по синтезу NМMО внедрена в Институте прикладной химии Армении (АРИАК). Ուսումնասիրվել է N-մեթիլմորֆոլին-N-օքսիդի սինթեզը և մշակվել է վերջինիս սինթեզի անթափոն տեխնոլոգիական գործընթացը: N-Մեթիլմորֆոլին-N-օքսիդի կիրառման կարևորագույն նշանակությունը կայանում է նրանում, որ այն իդեալական լուծիչ է հանդիսանում ցելյուլոզայի համար: N-Մեթիլմորֆոլին-N-օքսիդը լայն կիրառություն ունի ոչ միայն որպես լուծիչ, այլ որպես ելանյութ նուրբ օրգանական սինթեզներում: N-Մեթիլմորֆոլին-N-օքսիդի սինթեզի առաջարկվող տեխնոլոգիական գործընթացը մշակվել և իրականացվել է “ARIAK” Կիրառական քիմիայի ինստիտուտում: As an alternative to the viscose production, some amount of the cellulose fibers are produced by the lyocell process by dissolution of cellulose in a polar organic solvent ‒ N-oxide of N-methylmorpholine (NМMО) which has strong donor properties, forming hydrogen bonds with cellulose molecules, leading to swelling and dissolution. The area of usage of NМMО involves also its usage as a co-oxidizing agent in fine organic synthesis as well. Thus the development of the technological process for the synthesis of NMMO is an actual issue for the chemical industry. The first stage of the process – oxidation of N-methylmorpholine by the hydrogen peroxide at the temperature of 70°C for 2-6 hours is well known in the literature. The second stage is the crystallization of the product – NMMO monohydrate from the obtained aqueous solution. The procedure described in the literature, with the application of azeotropic distillation of water with benzene is not applicable for the large scale production as the final product is not sufficiently pure and does not have a marketable condition i.e. the NMMO monohydrate is not obtained as crystals. Other method suggests the usage of high boiling DMF for the crystallization. For the crystallization of NMMO we suggested the alternative way, by simple pouring of the reaction mixture from the bottom valve of the distillation apparatus into acetone, the white crystalline form of NMMO monohydrate is obtained. The regenerated acetone can be further used for the precipitation of NМMО. The presented technological scheme of the synthesis and precipitation of NMМО is implemented in the Armenian Institute of Applied Chemistry (ARIAC).
Keywords: Chemical technology